2023
DOI: 10.1186/s12937-022-00830-9
|View full text |Cite
|
Sign up to set email alerts
|

Online Arabic Beverage Frequency Questionnaire (ABFQ): evaluation of validity and reliability

Abstract: Background Obesity and chronic diseases are significant public health issues in the Middle East and North Africa region. A robust body of evidence demonstrated the association between beverage consumption, obesity, and chronic diseases. Therefore, the assessment of beverage consumption is gaining more interest in health policy development, food industry partnerships, research expansion and community involvement. Although beverage-consumption assessment tools have been developed for various popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The soft drink consumption per week among all the participants was (on average) 3.5 ordinary glasses with a standard deviation of 2.993 glasses, that is, a minimum average of 0.507 glasses to a maximum of 6.493 glasses. In Saudi Arabia, Aldhirgham, Almutairi, Alraqea, et al (2023) reported an average consumption of 3.43±0.62 glasses per week. However, most statistics on the subject refer to a consumption measure in per capita liters per person yearly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The soft drink consumption per week among all the participants was (on average) 3.5 ordinary glasses with a standard deviation of 2.993 glasses, that is, a minimum average of 0.507 glasses to a maximum of 6.493 glasses. In Saudi Arabia, Aldhirgham, Almutairi, Alraqea, et al (2023) reported an average consumption of 3.43±0.62 glasses per week. However, most statistics on the subject refer to a consumption measure in per capita liters per person yearly.…”
Section: Discussionmentioning
confidence: 99%
“…This research has merit since it provides new facts about Lebanese soft drink consumers based on highly reliable sample size. Researchers from Saudi Arabia and the United Arab Emirates (UAE), among others, conducted several studies (Benajiba and Mahboub, 2019;Islam, Al-Karasneh, Hussain, et al, 2020;Aldhirgham, Almutairi, Alraqea, et al, 2023;Nassar, Islam, Hasan, et al, 2023). In Egypt, Al-Askalany, Sadden, & Mohamed (2018) experimented with the impact of soft drinks on blood and liver in rats.…”
Section: Discussionmentioning
confidence: 99%